Frontal sinus fractures and cerebrospinal fluid leaks: a change in surgical paradigm. Issue 1 (February 2020) - Banks, Catherine; Grayson, Jessica; Cho, Do Yeon; Woodworth, Bradford A.
Abstract : Purpose of review: Traditionally, frontal sinus trauma has been treated using open incisions to access the anterior and/or posterior table. Mounting evidence indicates frontal sinus trauma can be managed using an endoscopic endonasal approach (EEA) with less morbidity. Such an approach permits preservation of a functional sinus and less reliance on computed tomography for postoperative follow up. The goal of this article is to highlight a shift in paradigm away from open approaches using external incisions towards an EEA to repair cerebrospinal fluid (CSF) leaks and fractures of the frontal sinus. Recent findings: In a prospective case series of 46 patients undergoing EEA to frontal sinus fractures, 41 patients had active CSF leaks arising from the posterior table of the frontal sinus. A successful endoscopic repair was achieved in 97.6% with only one patient requiring revision Draf IIB surgery. Anterior table fractures were also successfully reduced with excellent cosmesis. Summary: Endoscopic repair of frontal sinus fractures and CSF leaks is effective and well tolerated. In select patients, it is the preferred treatment as it maintains normal sinus structure and function, minimizing both early and late complications.